Depressing dependence? Transfers and economic growth in the German States, 1975-2005 - Thushyanthan Baskaran; Lars P. Feld; Sarah Necker (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2017)
Most countries pay substantial intergovernmental transfers to poor regions with the aim of achieving regional convergence. Consequently, transfers should have a positive effect on economic growth. However, it is equally possible that transfers perpetuate under-development. This paper studies empirically the effect of intergovernmental transfers on economic growth with a panel of West German states over the period 1975-2005. The findings suggest that transfers do not foster economic growth, presumably because the recipients use them to subsidize declining industries.
Keywords: H70; H73; H77; 330; intergovernmental transfers; economic growth; fiscal federalism